Combined metabolomics and proteomics analysis of vascular cognitive impairment in hypertensive rats induced by endothelial injury - Xiao Zhang; Surui Chang; Jiangang Liu; Dongling Wang (PLoS ONE, 2025)
Aim Based on metabolomics and proteomics research, we investigate the molecular biological mechanisms underlying vascular cognitive impairment (VCI) in rats induced by hypertension combined with endothelial damage, aiming to identify proteins or metabolites associated with key metabolic pathways. Methods SPF hypertensive rats (SHR) were used to damage the common carotid artery endothelium with microcurrent to induce vascular cognitive impairment model in rats (Model group), SHR rats (SHR group) and SPF normotensive Wistar-Kyoto rats (WKY) with the same genetic background were used as sham operation groups (no current stimulation after dissection), with 10 rats in each group. Morris water maze, PNT experiment and SPT experiment were used to detect the learning and memory ability of rats. TMT quantitative proteomics technology combined with liquid chromatography tandem mass spectrometry (LC-MS/MS) was used to detect the difference in metabolites and proteins in brain tissue of rats with vascular cognitive impairment. Results From Day 1–5, compared with the WKY group, both the Model and SHR groups exhibited shortened incubation periods and slower average swimming speeds (P < 0.01); On day 6, compared with the WKY group, the Model group showed a significant decrease in the number of platform crossings (P < 0.05), time spent in the target quadrant (P < 0.05), and total distance traveled in the target quadrant (P < 0.05). Pathological results revealed that, compared with the WKY group, the SHR group and Model group exhibited a decrease in the number of glial cells and neurons in the hippocampal tissue, with relatively loose arrangement of cell bodies and lighter Nissl staining. In the Model group, some hippocampal neurons changed from a granular to a powdery appearance, with nuclear pyknosis, accompanied by cellular edema and necrosis. The metabolomics results showed that there were 437 significantly different metabolites between the Model group and the WKY group, 128 (+) and 309 (-); there were 449 significantly different metabolites between the Model group and the SHR group, 119 (+), 330(-). The differential metabolites in each group were mainly concentrated in metabolic pathways such as alanine, aspartate and glutamate metabolism, arginine and proline metabolism, and amino acid biosynthesis. The proteomics results showed that compared with the WKY group, there were 141 differentially expressed proteins in the Model group, 55 (+), and 86 (-). Pathways with higher connectivity in the action network include “glycine, serine and threonine metabolism”, “phenylalanine metabolism”, etc.; compared with the SHR group, there were 28 differentially expressed proteins in the Model group and 15 (+). 13 species (-). The significantly enriched pathways are “focal adhesion” and “relaxin signaling pathway”. Conclusion Rats with hypertension combined with endothelial injury have behavioral disorders, which are similar to the causes and signs of clinical vascular cognitive impairment; the biological mechanisms manifested in the model involve amino acid metabolism disorders, energy metabolism, relaxin signaling pathway and impaired focal adhesion function. Characteristic metabolites in the model group, such as ATP, cAMP, Creatine, Cyanocobalamin, Dopamine, Serotonin, Tryptophan, Uric acid and Vitamin B1 decreased, while GABA, Glucose, Isocitrate and Malate increased.